2020
DOI: 10.1177/1527476420919702
|View full text |Cite
|
Sign up to set email alerts
|

Media Studies and the Pitfalls of Publicity

Abstract: For many academics, using social media has both drawbacks and advantages. Social media may allow connection with colleagues, scholarly promotion, and public engagement, and may also open researchers up to criticism and even possible harassment. This essay argues that we must think critically about logics of self-branding and attention-seeking given these two sides of the coin of social media publicity. First, publicity can easily be weaponized against scholars engaging in projects that may be socially or polit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…First, publicity can easily be used as a weapon against negative sentimental netizens who may be socially or politically controversial [14]. Social media can enable connections with colleagues, scientific promotion, and public engagement, and can also open up criticism and even the possibility of harassment, self-branding, self-image, and attention-seeking [15]. Promotional publicity as new and more productive thinking about the effects of interactions on organizations develop [16].…”
Section: Publicity Recorded On Online Mediamentioning
confidence: 99%
“…First, publicity can easily be used as a weapon against negative sentimental netizens who may be socially or politically controversial [14]. Social media can enable connections with colleagues, scientific promotion, and public engagement, and can also open up criticism and even the possibility of harassment, self-branding, self-image, and attention-seeking [15]. Promotional publicity as new and more productive thinking about the effects of interactions on organizations develop [16].…”
Section: Publicity Recorded On Online Mediamentioning
confidence: 99%
“…As a novice researcher and research communicator, upon pitch acceptance I found myself at the bottom of a steep, time-sensitive learning curve that was daunting, given I had no mentors to seek guidance from. As noted by Marwick (2020), 'the ability to translate aforementioned difficult, mentally taxing research into easily digestible soundbites, tweets, or simply editorials is by no means universal' (p. 609), and writing Plain Language pieces offers unique challenges.…”
Section: Accessiblementioning
confidence: 99%
“…Universities may still focus on supporting the production of scholarly outputs, poorly facilitating the production of translational outputs (Merga & Mason, 2020b). Furthermore, these efforts may not be recognized, as ‘even universities which explicitly include “public scholarship” in their tenure and promotion guidelines still emphasize traditional forms of scholarship over public impact’, despite the fact that ‘Twitter accounts, YouTube videos, or free, publicly available white papers may reach far more people, and have much more impact, than any type of scholarly output, no matter how rigorous’ (Marwick, 2020, p. 609).…”
Section: Introductionmentioning
confidence: 99%
“…There’s dialogue here between on the one hand doubling-down on harnessing media studies’ foundational offerings of interdisciplinarity, criticality, and openness (see, for example, Dencik, this issue; Ewen, this issue; Henderson, this issue; Lim, this issue; Mayer, this issue; Shimpach, this issue), and on the other hand, finding new ways of disrupting unhelpful norms, better supporting, and mentoring junior and underrepresented colleagues and students, and standing up in solidarity for those who are vulnerable to coordinated hate campaigns or anti-intellectual movements (see, for example, Andrejevic, this volume; Marwick, this volume; Orgad, this volume; Poell, this volume). Doubtless this will entail both re-engaging with key texts and historical moments (see Leonard, this issue; Tasker, this issue), and maintaining a commitment to intermediality (see Johnson, this issue) as well as theorizing challenging new objects and phenomena (O’Neill, this issue; Shapiro, this issue).…”
mentioning
confidence: 99%
“…Media studies, research, whether undertaken from a social sciences or a humanities faculty, needs to continue in its serious reckoning with how cleavages of race, gender, sexuality, and nationality construct a privileged few as “experts” while others (likely women, people of color) become targets of “networked harassment” (see Marwick, this issue). We should also be closely monitoring how the pandemic moment differently impacts our different academic departments and colleagues.…”
mentioning
confidence: 99%